Climate Risk and Vulnerability (CR&V) assessment for climate services: Rice-fish production and value chain - Ayeyarwady Delta, Myanmar - Thant, Phyu Sin; Khaung, Ye; Akester, Michael J.; Giles, James; Swaans, Cornelis (2023)
As part of the CGIAR initiative Asian Mega-Deltas, a scoping study was completed by the end of 2022 to prioritize key delta-oriented production systems and value chains in Myanmar's Ayeyarwady Delta (Gonsalves et al., 2022). Rice, rice-fish and pulses production systems and value chains were selected based on a set of criteria including production, economic and nutritional value, climate change impact, and potential benefit of climate services with specific attention to the role of women and smallholders. To better understand the selected commodity production systems in the Ayeyarwady Delta, an additional value chain, climate risk and vulnerability assessment was made. This report focuses on rice-fish production and its value chain. This report aims to study the selected rice-fish production and value chain in the Ayeyarwady Delta to gain a deeper understanding of the following: 1) General characteristics and relative importance of the production system and value chain across the delta, 2) Value chain components, their relations, and key actors, 3) Climate risks, vulnerabilities and impacts across the value chain, 4) Climate information and complementary services and 5) Enabling environment (institutions, policy, etc.)